Using discrete event simulation to explore food wasted in the home. Issue 4 (4th July 2022) - Kandemir, Cansu; Reynolds, Christian; Tom, Quested; Fisher, Karen; Devine, Rachel; Herszenhorn, Estelle; Koh, S.C. Lenny; Evans, David
ABSTRACT: Food waste is an issue of global importance. Households generate more food waste than any other source in high- and middle-income countries. There are many solutions to reduce household food waste, but measurement of the impact of each solution is costly, and therefore usually not undertaken. This is a major barrier to decision makers adopting the most effective solutions. Discrete event simulation (DES) modelling is ideally placed to overcome these problems. This paper presents the most developed application of DES to household food waste to date: The Household Simulation Model (HHSM). The HHSM has the flexibility to model several food items. It includes many household dynamics that can affect food waste (e.g., purchasing, storage, consumption). The HHSM simulates a range of household types to reflect the diversity of the population in question (for this paper, the United Kingdom). This paper demonstrates the innovation of the HHSM: it provides a framework allowing different types of evidence to be brought together to help understand how food waste is influenced by a range of factors. To illustrate its usefulness, we provide an analysis of six potential interventions to reduce milk waste, covering both product innovation and behaviour change.